L'éducation spirituelle ou l'autre de la pédagogie ? - Philippe Filliot
By taking the way of spiritualities (particularly eastern and far-eastern ones) the matter in hand is to try to see the questions about education from a different angle and thus thinking pedagogy differently. Research developments, in a multi-referential way, concern four ways, considered from a pedagogic point of view: yoga, Chinese wisdoms, zen Buddhism, and Christian religion. Our hypothesis is that there is, in this spiritualities which are in the same time dissimilar and coherent, a specific philosophy of education -even though there is no such philosophy yet - that remains to be updated. Outside scholarship, how can we define the triangular relationship between the teacher, the pupil, and knowledge? Can we identify, beyond historic and cultural specificities, a new way of thinking, which would be characteristic of what we call spiritual education?